Prevention of Cardiovascular Disease: Screening for Magnesium Deficiency - Paolo Severino; Lucrezia Netti; Marco Valerio Mariani; Annalisa Maraone; Andrea D’Amato; Rossana Scarpati; Fabio Infusino; Mariateresa Pucci; Carlo Lavalle; Viviana Maestrini; Massimo Mancone; Francesco Fedele (Cardiology Research and Practice)
Magnesium is an essential mineral naturally present in the human body, where it acts as cofactor in several enzymatic reactions. Magnesium is a key cardiovascular regulator, which maintains electrical, metabolic, and vascular homeostasis. Moreover, magnesium participates in inflammation and oxidative processes. In fact, magnesium deficiency is involved in the pathophysiology of arterial hypertension, diabetes mellitus, dyslipidemia, metabolic syndrome, endothelial dysfunction, coronary artery disease, cardiac arrhythmias, and sudden cardiac death. In consideration of the great public-health impact of cardiovascular disease, the recognition of the negative effects of magnesium deficiency suggests the possible role of hypomagnesaemia as cardiovascular risk factor and the use of serum magnesium level for the screening and prevention of cardiovascular risk factors and cardiovascular diseases. Moreover, it might help with the identification of new therapeutical strategies for the management of cardiovascular disease through magnesium supplementation.